Taxonomical revision of Campylocentrum sect. Dendrophylopsis Cogn. (Orchidaceae-Vandeae-Angraecinae) - Pessoa, Edlley; Alves, Marccus (Phytotaxa, 2016)
This study reviews the leafless species of Campylocentrum, which belong to section Dendrophylopsis. Thirteen species are recognized. While the section has a wide distribution in the Neotropics, a majority of the species are known only from the type specimens or a few additional collections, suggesting a restricted distribution range. Members of Dendrophylopsis are easily distinguished but determination to species level is complicated by the low number of vegetative characters and similarity of the flowers, as well as the lack of a taxonomic revision of the group. These circumstances result in frequent misidentifications. This study provides typifications, complete synonymies, conservation statuses, complete descriptions, illustrations, distribution maps and an identification key to the species in question.